Computational analysis of homo-dimerization of chloroplast-localized chaperonin from the alga Chlamydomonas reinhardtii - Wongsamart, Rungdawan; Kiriwan, Duangnapa; Suwattanasophon, Chonticha; Yokthongwattana, Kittisak; Choowongkomon, Kiattawee (Agriculture and Natural Resources, 2021)
Molecular chaperones are major groups of proteins responsible for proteostasis regulation. GroEL is a protein belonging to the chaperonin family of molecular chaperones. Unlike GroEL in prokaryotes, chloroplast chaperonin 60 (Cpn60) has distinct subunits. The chaperonin for the alga Chlamydomonas reinhardtii has one α and two β subunits (β1 and β2). Even though a crystal structure of homo-oligomer (Cpn60β1) has been reported, it is still unclear how these subunits assemble. This study modeled homo-subunit dimers of C. reinhardtii. Dimers αα, β1β1 and β2β2 were analyzed based on molecular dynamics simulation. Many hydrogen bonds presented in the same position among the three dimers, even though the amino acids were different. Charged amino acids were an important factor influencing the binding interface orientation. The binding free energy of the β1β1 dimer was the lowest, followed by β2β2 and αα, respectively. The results suggested that the β1β1 assembly was more favorable than β2β2 and αα.